The forgotten 500 : the untold story of the men who risked all for the greatest rescue mission of World War II - Freeman, Gregory A. (Nal Caliber, 2007)
In 1944 the OSS set out to recover more than 500 airmen trapped and sheltered for months by villagers behind enemy lines in Yugoslavia. Classified for over half a century for political reasons, the full account of Operation Halyard, a story of loyalty, self-sacrifice, and bravery, is now being told for the first time.--From publisher description.